Filsafat Politik Barat dan Masalah Keadilan: Catatan Kritis atas Pemikiran Will Kymlicka - Wahyudi, Agus (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2004)
Justoce has dominated contemporary debates in the Western political philosophy for the last couple of decades. The book writtern by Will Kymlicka, Contemporary Political Philosophy: An Introduction is a clear example of this development. The book is worth appreciating as this provides deep and extensive discussions of theories of justice.This essay examines Kymlicka's argument, that is even through modern political theories such Ultilitarianism, Liberal Equality, Libertarianism, Marxism, Communitarianism, and Feminism seem to appeal to conflicting values, they have no different foundational values, as they are all egalitarian theories, which is understood in terms of treating people as equals. This essay suggets that there is a truth in this notion and thus such kinds of theory need to be thoroughly studied, even though there is also a need to develop a theory that is roored in a particular context.